2018
DOI: 10.1111/jfpp.13621
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the usage of unsaturated fatty acid-rich and low-calorie oleogels as a shortening mimetics in cake

Abstract: In the present study, two purposes were aimed: (a) Reduction of fat content of cakes using watery oleogels and (b) Reduction of saturated fatty acid contents of cakes using oleogels rich in unsaturated fatty acid composition instead of shortening. For this aim, five different oleogels were produced using different percentages of high oleic sunflower oil, cotton seed oil, and blend fat and they were used in the cake formulation instead of shortening. Some physicochemical properties of oleogels (solid fat conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 31 publications
5
59
0
1
Order By: Relevance
“…Then, the obtained mixtures with different monostearin concentrations (4, 6, 8, 10, and 12%, w/w) were stored in an incubator at 4 or 20°C for 12 hr, respectively. The lowest concentration of monostearin for forming the oleogels was determined by the invention vial method (Pehlivanoglu et al, ). The physicochemical properties of the oleogels were characterized using the following techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the obtained mixtures with different monostearin concentrations (4, 6, 8, 10, and 12%, w/w) were stored in an incubator at 4 or 20°C for 12 hr, respectively. The lowest concentration of monostearin for forming the oleogels was determined by the invention vial method (Pehlivanoglu et al, ). The physicochemical properties of the oleogels were characterized using the following techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Cake batters are oil-in-water emulsions, the continuous aqueous phase containing dissolved or dispersed non-fat ingredients (flour, sugar, salt, yeast, and milk powder). For the aim of lowering the caloric value and the fat content of the cakes, watery oleogels were prepared-a reduction of saturated fatty acid contents and an increase in unsaturated fatty acids being obtained [72]. Oleic sunflower oil, cottonseed oil, and fat blend were gelled with 5% carnauba wax, water-free oleogels, as well as watery oleogels (emulsified) being prepared.…”
Section: Cakes and Baked Goodsmentioning
confidence: 99%
“…Some physicochemical properties of oleogels, the rheological properties of the batters and the volume, structure, appearance, color, and sensory properties of cakes containing oleogel were also analyzed and compared to a reference. The sensorial analysis indicated that the panel considered the oleogel cakes acceptable, while the most preferred were the cakes containing oleogel of high oleic acid sunflower oil and cottonseed oil in equal amounts [72].…”
Section: Cakes and Baked Goodsmentioning
confidence: 99%
“…Oleogels are products of solidifying vegetable oils using natural wax esters [56,57,58,59]. The oleogelation process forms waxy crystal structure which hold liquid oil within a solid matrix, which allows the use of liquid vegetable oils in place of shortening.…”
Section: Summary Of the Current Fat Replacers Used In Baked Productsmentioning
confidence: 99%